2004
DOI: 10.1136/bmj.37957.560278.ee
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome of singletons and twins after assisted conception: a systematic review of controlled studies

Abstract: Objective To compare the perinatal outcome of singleton and twin pregnancies between natural and assisted conceptions. Design Systematic review of controlled studies published [1985][1986][1987][1988][1989][1990][1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002]. Studies reviewed 25 studies were included of which 17 had matched and 8 had non-matched controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
618
10
39

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 986 publications
(711 citation statements)
references
References 34 publications
(116 reference statements)
44
618
10
39
Order By: Relevance
“…Even if some initial studies suggested that the risk of congenital malformation after IVF-ICSI is higher in twins compared to spontaneous twin pregnancies, this has not been subsequently confirmed [17,2]. A confounder here is that birth defects are increased per se in twin pregnancies, in particular if monozygotic [4,2].…”
Section: Discussionmentioning
confidence: 91%
“…Even if some initial studies suggested that the risk of congenital malformation after IVF-ICSI is higher in twins compared to spontaneous twin pregnancies, this has not been subsequently confirmed [17,2]. A confounder here is that birth defects are increased per se in twin pregnancies, in particular if monozygotic [4,2].…”
Section: Discussionmentioning
confidence: 91%
“…Different studies have shown that children born after assisted reproductive techniques (ART) have poorer outcomes in terms of preterm birth (PTB), low birth weight (LBW), small for gestational age (SGA), and perinatal mortality when compared with newborns of natural conceptions [54][55][56]. Among those undergoing IVF, the results between fresh and frozen embryo transfers (FET) in obstetric perinatal outcome terms are still unclear [57][58][59].…”
Section: Freeze-all-why?mentioning
confidence: 99%
“…This approach, however, is associated with a number of risks including ovarian hyperstimulation syndrome and increased cost due to the high doses of medications used. Furthermore, the practice of transferring more embryos carries the risk of multiple gestations, which is associated with increased maternal and perinatal morbidity and mortality [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%